Secrecy Performance of Dual-Hop Energy Harvesting NOMA Network with Alamouti/RAS Technique - Demirkol, Büşra; Kucur, Oğuz; Kurt, Güneş Karabulut (Institute of Electrical and Electronics Engineers Inc., 2025)
This study presents the secrecy outage performance (SOP) of the Alamouti/receive antenna selection (RAS) technique in a dual-hop non-orthogonal multiple access (NOMA) network taking advantage of simultaneous wireless information and power transfer (SWIPT). In the studied system, a base station (BS) using Alamouti coding serves multiple antenna users applying RAS simultaneously via energy harvesting (EH) enabled amplify-and-forward (AF) relay in the presence of an eavesdropper (EVE) applying maximum-ratio combinig (MRC). The SOP for users is presented through Monte Carlo simulations over Rayleigh fading channels. © 2025 Elsevier B.V., All rights reserved.
Alamouti/RAS Teknigi ile Iki Atlamali Enerji Hasatlamali NOMA A?ginin Gizlilik Performansi
33rd IEEE Conference on Signal Processing and Communications Applications, SIU 2025 -- Istanbul; Isik University Sile Campus -- 211450
Keywords: Alamouti space time block coding; non-orthogonal multiple access; receive antenna selection; Secrecy outage probability; simultaneous wireless information and power transfer